2014
DOI: 10.3109/03014460.2014.968206
|View full text |Cite
|
Sign up to set email alerts
|

Association of ACE, FABP2 and GST genes polymorphism with essential hypertension risk among a North Indian population

Abstract: It is concluded that ACE (rs 4646994), FABP2 (rs1799883) and GST (GSTM1 null or positive genotype and GSTT1 null or positive genotype) genes polymorphism are associated with HTN. Further investigation with a larger sample size may be required to validate this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 47 publications
1
10
2
1
Order By: Relevance
“…The frequencies of the GSTT1-and GSTM1-null genotypes among hypertensive patients in the current study (14.69% and 34.78%, respectively) were lower in comparison to findings from Arab (30.00% and 60.00%, respectively), Chinese (58.10% and 60.00%, respectively) and Korean (55.40% and 51.80%, respectively, and 61.20% and 62.40%, respectively) populations, but similar to findings from another North Indian study (11.59% and 34.05%, respectively). 15,[33][34][35][36] In comparison, the GSTM1-positive genotype was found in 65.22% of the hypertensives in the current study; this was higher than the results from Arab (40.00%), Chinese (40.00%) and Korean (48.20% and 37.60%) populations, but again similar to results from a North Indian study.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…The frequencies of the GSTT1-and GSTM1-null genotypes among hypertensive patients in the current study (14.69% and 34.78%, respectively) were lower in comparison to findings from Arab (30.00% and 60.00%, respectively), Chinese (58.10% and 60.00%, respectively) and Korean (55.40% and 51.80%, respectively, and 61.20% and 62.40%, respectively) populations, but similar to findings from another North Indian study (11.59% and 34.05%, respectively). 15,[33][34][35][36] In comparison, the GSTM1-positive genotype was found in 65.22% of the hypertensives in the current study; this was higher than the results from Arab (40.00%), Chinese (40.00%) and Korean (48.20% and 37.60%) populations, but again similar to results from a North Indian study.…”
Section: Discussionsupporting
confidence: 82%
“…The insertion/insertion genotype frequency in the combined North Indian hypertensive population of the current study (28.07%) was similar to that found in hypertensive Pakistanis (29.30%) and another North Indian population (28.62%). 15,25 There was a significant association between the ACE insertion/insertion genotype and hypertension; this contrasts with the results of a study conducted among South Indians, although it is similar to that of the other study on North Indians. 15,26 The current study found an association between the ACE deletion/deletion genotype and hypertension, although this was not significant.…”
Section: Discussioncontrasting
confidence: 74%
See 3 more Smart Citations